Free Healthcare Scheme and the Health Status of Older Persons: A Cross-sectional Study in Selected Districts in Tanzania - John Magata, Rygon; Haule, Kelvin; Kaswamila, Abiud (Tanzania Journal for Population studies and Development, 2025)
Free healthcare schemes have drawn attention to many countries especially when the number of older persons is increasing worldwide. In Tanzania, the establishment of the scheme in 1994 aimed at protecting older persons from medical expenses at public healthcare facilities. Despite the aim, there have been limited studies on the health status of older persons. The study used a cross-sectional survey design involving older persons from Nachingwea and Kilwa districts who were randomly selected for the study. Data were collected by using individual households survey, key informants interview, focus group discussion, and documentary reviews. The statistical package for social sciences (SPSS) was used to analyse quantitative data, while content analysis was used to analyse qualitative data. The study found that, the health status of older persons was poor, as the majority 61% (n = 369) had poor self-rated health (SRH). The prevalence of non-communicable diseases (NCDs) was high among older persons, as the majority 82.66% (n = 369) reported having one or more NCDs, with hypertension being the most prevalent 72.36%. The poor SRH was statistically significant association with the provision of medication (X2 = 8.2542, p < 0.005) and diagnosis services (X2 = 6.8891, p < 0.005). The findings conclude that the overall health status of older persons who utilized free healthcare was poor due to lack of free medications and diagnosis services. The study recommends for clear policies and guidelines for free healthcare for older persons, continuous health education, and establish free screening for NCDs at community levels.